Superiority claims in advertisements: What you should know / Kamisah Hj Ariffin, Norazlan Anual - Ariffin, Kamisah; Anual, Norazlan (2005)
Advertising is an essential element in the marketing process. It plays the role in carrying out the promotion of a product. However, the development of technology has led to mass production of the same product brand, which in turn, has resulted in tough competition among the product manufacturers. Thus, copywriters have employed a myriad of techniques to persuade the consumers to arrive at the desired action, that is, to choose and buy the product. One of the most common techniques is to claim the superiority of the product. This may be achieved by exaggerating the facts or creating an illusion of superiority through the use of superlative or laudatory words. Consumers may be easily deceived by the use of language into believing the claims made for the products without looking for any evidence to substantiate them. This is the main focus of the paper - to raise consumers' awareness of such tactics by identifying the words and phrases used by copywriters that have the tendency to mislead or deceive. In turn, they can be more informed, thus, discerning in making decisions in purchasing a product.